Joining the Spirit: Missio Dei and artificial intelligence in digital missional praxis - Niemandt, Cornelius J. P. (HTS teologiese studies, 2025)
As artificial intelligence (AI) reshapes the digital landscape, can we discern the movement of the Spirit within this transformation? This research argues that AI developments, often seen as alien to spiritual mission, fall within the Triune God’s realm and align with the missio Dei. By tracing the Gospel’s historical adoption of evolving technologies – from the Incarnate Word to the Written, Proclaimed and now Digital Word – we propose AI as the latest iteration in God’s unfolding mission. The study first examines the compatibility between missio Dei and AI, asserting that AI, as part of creation, invites missional engagement rather than retreat. Using Heyns’ framework of various expressions of God’s Word – creation, sustenance, redemption, incarnation, Scripture, proclamation and now the Digital Word – the research shows that AI is a natural extension of God’s revelatory presence through innovation, and presents a way to participate in the mission of the Spirit. Next, the article explores AI’s role in a rapidly globalising digital culture. This paradigm shift transforms self-perception and communication, creating opportunities and challenges for contextualised missions. The Gospel must be incarnated in ways that resonate with digital cultures, reflecting theology’s ongoing adaptation to cultural shifts. Attention is given to Digital Ecclesiology, investigating how AI is reshaping church practices, virtual communities and online worship. The study also examines AI’s intersection with mission and creativity, arguing that AI should serve rather than replace human creativity, fostering deep connection, beauty and truth. Artificial intelligence’s potential as a tool for discipleship and formation is explored, assessing its role in personalised theological education, virtual fellowship and global outreach.Contribution: The concept of mission from the margins provides a critical lens, calling for humility and attention to often overlooked voices. Those on society’s edges offer insights into exclusionary structures, challenging AI’s potential centralising tendencies.